THE EFFECT OF DELAYED TIME OF OSCILLATION IN THE LOGISTIC EQUATION - Ivone Lawrita; Efendi .; Ahmad Iqbal Baqi (Jurnal Matematika UNAND, 2013)
Time delay logistic equation is a modification of the logistic equation. Theequation logistic delay time can affect the increase and decrease in population. This leadsto oscillations in the equation. The purpose of this research is to study the oscillation ofthe logistic equation with time delays.